Projektpedagógia a gyakorlatban - A VIZED projekt gyakorlati elemei és hatékonysága mint a társadalmi változás csírája - Schnell, Zsuzsanna; Zalay, Szabolcs; Gombás, Ildikó (Kultúratudományi Szemle, 2023)
The article describes the realisation of a project in the framework of environmental and health education at Leőwey High School in Pécs. We outline the method’s basic steps and notions that ensure a valid and reliable pedagogical scheme indispensable for the educative purpose of the project method. The skills developed in the method are listed, evaluated and described, all converging to enhance 21st century competencies with which one can educate competent individuals for the future, for life, an example of ‘homo studens’, aiming to raise wise and socially competent, knowledgeable individuals, humans for life. In this, the recognition and support of individual inclinations are essential, where the educator takes the role of a moderato, rather than providing rready-bakedlexical knowledge as in the traditional frontal classroom setting. The article also describes the compulsory elements and phases of projects, thus giving a guide to further projects with applied nature and with educational potential to foster and bring on social change.